Turkey pox virus characterization from recurring infection in Egypt - Elgharbawy, Yusuf A.; Ali , Saad S.; El-Nahas, Ehab M.; Ali, Mervat M. (Journal of Advanced Veterinary Research, 2024)
Poxvirus infections of avian species worldwide are caused by viruses of a single genus (Avipoxvirus), they belong family Poxviridae. The turkey pox virus (TKPV) is one of the most serious illnesses and a major source of financial losses for the developing turkey industry. Even though the fowl pox virus vaccine is used to prevent the disease, TKPV still creates significant economic difficulties, therefore isolating and adapting the virus is crucial for the development of homologous vaccines that will manage the illness. In the summer of 2021, the TKPV disease spread to numerous farms inside the Giza Governorate. Ten samples of skin lesions from various farms were gathered and given labels. In accordance with Koch's postulates, the collected samples were ground, homogenized, and centrifuged to extract supernatant, which was then injected into healthy birds to confirm the disease symptoms and susceptibility. For more confirmation the virus was isolated on embryonated chicken egg (ECE) through chorio-allantoic membrane (CAM) route at 10 day old after 5 to 6 days of inoculation the pock lesion appeared A fragment of the P4b gene coding for DNA polymerase core protein of TKPV was amplified by PCR then sequenced. A newly discovered isolate of field-isolated TKPV was revealed by phylogenetic analysis to have high similarity (between 96% and 100%) with the sequences that have been published. The new isolate of Turkey pox virus strain MKP 334 core protein (P4b) gene (with Accession No. MZ983434.1 in GenBank) has 100% to MG787222.1 Turkey pox virus isolate TurPVIR12 p4b gene and differ from the only isolated strain of TKPV that isolated at 2020 in Mansoura (MT219997.1 Turkey pox virus strain mans17T P4b 2020 EGYPT) but they have 99.6 identity.